Maximum and anti-maximum principle for the fractional p-Laplacian with indefinite weights - ASSO, Oumarou; CUESTA, Mabel; DOUMATE, TELE JONAS; LEADI, LIAMIDI ARÈMOU (My University, 2024)
We establish some non-resonance results and maximum and anti-maximum principles for a quasilinear non local problem involving the fractional p-Laplacian operator perturbed by an indefinite potential.
Keywords: Fractional p-Laplacian; Indefinite weights; Maximum principle; Non-resonance; Anti-maximum principle